Edge‐Enriched Mo2TiC2Tx/MoS2 Heterostructure with Coupling Interface for Selective NO2 Monitoring. (25th June 2022) - Zhao, Qiuni; Zhou, Wenzhe; Zhang, Mingxiang; Wang, Yang; Duan, Zaihua; Tan, Chaoliang; Liu, Bohao; Ouyang, Fangping; Yuan, Zhen; Tai, Huiling; Jiang, Yadong
Abstract: Endowed with rich terminal groups, good electrical conductivity, and controllable structure, transition metal carbides/nitrides (MXenes) have attracted extensive attention for potential application in gas sensor, but long‐standing challenges of the MXenes (titanium carbide as the representative) are their limited selectivity and sensitivity. Herein, a high‐active double transition‐metal titanium molybdenum carbide (Mo2 TiC2 T x ) with superstrong surface adsorption (−3.12 eV) for NO2 gas molecule is proposed, and it is further coupled with molybdenum disulfide (MoS2 ) by interface modulation to construct an edge‐enriched heterostructure. Due to the synergistic effect of strong adsorption, rich adsorption sites, and coupling interface of Mo2 TiC2 T x /MoS2 composite, the as‐fabricated Mo2 TiC2 T x /MoS2 gas sensor exhibits an outstanding response toward NO2 with high selectivity against various interference gases, which is well supported by density functional theory calculations. Meanwhile, the sensor exhibits a sensitivity of 7.36% ppm −1, detection limit of 2.5 ppb, and reversibility at room temperature. A portable, wireless NO2 monitoring system is demonstrated for gas leakage searching and dangerous warning based on Mo2 TiC2 T x /MoS2 gas sensor. This work facilitates the gas sensing application of MXenes, and provides an avenue for the development of wireless sensing system in environmental monitoring and safety assurance. Abstract : Combining strong adsorption of Mo2 TiC2 T x with edge‐enriched structure of MoS2, a Mo2 TiC2 T x /MoS2 heterostructure with coupling interface is proposed to develop the NO2 gas sensor with high selectivity and sensitivity. Moreover, a wireless NO2 gas monitoring system is demonstrated for gas leakage searching and dangerous warning in unmanned cruise, which expands the application of DTM MXene in sensing system.